2010
DOI: 10.1105/tpc.109.072736
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Plant Interactomes Using Literature Curated and Predicted Protein–Protein Interaction Data Sets

Abstract: Most cellular processes are enabled by cohorts of interacting proteins that form dynamic networks within the plant proteome. The study of these networks can provide insight into protein function and provide new avenues for research. This article informs the plant science community of the currently available sources of protein interaction data and discusses how they can be useful to researchers. Using our recently curated IntAct Arabidopsis thaliana protein-protein interaction data set as an example, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
(44 reference statements)
0
28
0
Order By: Relevance
“…In other words, their method can be easily applied, not only to yeast but to other species with less known localization and/or interaction information. Actually they predicted subcellular localization of fly, human, and Arabidopsis (Lee et al, 2008;Lee et al, 2010b) using protein interactions. The results of both works showed that the prediction worked well for the other organisms and could find real localizations of some unknown proteins (Figures 6-7).…”
Section: Results Of Location Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, their method can be easily applied, not only to yeast but to other species with less known localization and/or interaction information. Actually they predicted subcellular localization of fly, human, and Arabidopsis (Lee et al, 2008;Lee et al, 2010b) using protein interactions. The results of both works showed that the prediction worked well for the other organisms and could find real localizations of some unknown proteins (Figures 6-7).…”
Section: Results Of Location Predictionmentioning
confidence: 99%
“…Generated models for the location prediction for Fly (A), Human (B), and Arabidopsis (C) (adapted from Lee et al, 2008 andLee et al, 2010b). …”
Section: Other Network-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to an empirical estimation of the size of the protein interactome, experimentally determined interactions represent a small fraction (approximately 6%) of the entire protein interactome, and the relationships among most proteins remain to be discovered (Arabidopsis Interactome Mapping Consortium, 2011). To complement existing experimental resources, genomewide plant PPI networks have been developed by computational approaches (Cui et al, 2008;Lee et al, 2010;Lin et al, 2011;Wang et al, 2012Wang et al, , 2014. However, these methods attempt to predict PPIs using only nonstructural information.…”
mentioning
confidence: 99%
“…(31). Previously, we observed that the co-occurrence of sequence, structure, or function between a protein and its interacting partners is a strong predictor of joint subcellular location (32). We applied forward selection to choose feasible feature sets of high predictive power from the pool of generated individual and network protein features, with a network neighborhood restricted to nearest neighbors within distance 2, using a divide-and-conquer k-nearest-neighbor method (Fig.…”
mentioning
confidence: 99%